Forecasts of Wave-Induced Coastal Hazards in the United States Pacific Islands: Past, Present, and the Future - Guiles, Martin; Azouri, Assaf; Roeber, Volker; Iwamoto, Melissa M.; Langenberger, Fiona; Luther, Douglas S. (Frontiers in Marine Science, 2019)
This paper summarizes the existing coastal hazard forecast methods of PacIOOS, such as wave-induced run-up, by focusing on the critical components that need to be addressed in order to improve these forecasts and make them more accurate and available to broader coastal communities. We then propose that a horizontally, two-dimensional numerical modeling approach method should be adopted for developing future wave-induced coastal forecasts. To reach a future in which real-time two-dimensional model-based forecasts are a reality, we identify existing technologies that could lead to improvements, such as: (i) more accurate, accessible and frequently updated bathymetry and topography datasets; (ii) increased computational and software capabilities; and, (iii) more accurate sea level datasets. These advances, combined with crowdsourced-based model-data validation, will result in faster and more accurate forecasting tools that could greatly benefit coastal communities in need of more efficient risk mitigation programs.